PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD (STUDENT TEAMS ACHIEVEMENT DIVISION) SEBAGAI UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS XI IPA 7 SMA N 2 DENPASAR TAHUN PELAJARAN 2018/2019 - Wirasti, Komang (LPPM IKIP PGRI Bali, 2019)
The purpose of this research is to find out the improvement of mathematics learning outcomes by applying the STAD (Student Teams Achievement Division) cooperative learning model for students of class XI IPA 7 of SMA N 2 Denpasar in the academic year 2017/2018. This type of research is a collaborative Classroom Action Research (CAR) designed with two cycles, each cycle consisting of three meetings. The subjects of this study were students of class XI IPA 7 of SMA N 8 Denpasar in the 2018/2019 academic year, totaling 38 students, consisting of 17 male students and 21 female students. The object of this research is the application of the STAD type cooperative learning model and learning outcomes. Data collection methods used in this study are the test method, observation method, and documentation method. The results of the study in the first cycle, the number of students who completed in the first cycle was 46.15% and 53.85% incomplete, with an average score of student learning outcomes 74.80 and the absorption of students 74.80%. An increase in the average learning outcomes of students by 3.92 in cycle I. In cycle II, the number of students who completed in cycle II and the absorption of students 81.92%. The increase in the average learning outcomes of students by 7.12 ie from 74.80 in the first cycle to 81.92 in the second cycle. The average percentage of students' activities in class XI IPA 7 of SMA N 2 Denpasar experienced an increase of 11.88% ie from 51.12% in the first cycle which was quite active to 63% in the second cycle.